IMPLEMENTASI MANAJEMEN RISIKO KOMPREHENSIF UNTUK STABILITAS DAN PERTUMBUHAN BERKELANJUTAN - Alindra Yanuardi; Zaki Bahrun Ni’am; Luqman Fauzi (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2025)
This research is motivated by the urgency of implementing effective risk management in minimizing potential risks in financing. The purpose of this study is to identify the concept of risk management planning, risk management organizational structure, and risk management monitoring system implemented in Bank Syariah Indonesia. Through a comprehensive literature study approach by reviewing related journals and books, this study aims to examine the implementation of risk management in the Islamic bank. The results of the study concluded that the implementation of proper financing risk management can significantly reduce the potential for errors and risks that can have a negative impact on the sustainability of Islamic banking operations in the long term, thus emphasizing the importance of continuous adjustment and adaptation in dealing with various conditions and situations.